Reality and scientific theology - Torrance, Thomas Forsyth, 1913-- (Edinburgh : Scottish Academic Press, 1985)
In this book the author argues for a rigorous scientific theology under the double constraint of the reality of God and the reality of the world of space and time. Careful attention is given to the common commitment of theological and natural science to objective knowledge, and the deeply natural relation between knowledge of God the Creator and knowledge of the world he has made. Stress is laid upon the stratified structure of theology and the need for a radical simplification and unification of Christian doctrine. Is theology the 'science of God', and is it concerned with objective knowledge like natural science? Is there a natural theology and how is it related to knowledge of God through divine relation? How is the community of faith within which dogmatic theology arises related to the social coefficient of scientific inquiry? What is the place of mysticism and of art in theology? Does theology have a special notion of truth, and does it have its own inner logic and structure? These are some of the main questions which this book seeks to answer.
The Trinitarian structure of theology